Comparison of Candida albicans colony amount in heat-cured acrylic and thermoplastic nylon resin after immersion in Ulee Kareng coffee (Coffea robusta) - Sundari, Iin; Andayani, Ridha; Harahap, Novriyanti Fatimah (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Heat-cured acrylic resin is the most often used material in the manufacture of denture base. Along with the development of science and technology, to overcome the shortcomings of heat-cured acrylic resin, repairment of denture base material was done, one of them is a thermoplastic nylon resin. On the use of denture often found Candida albicans attached to the denture. This study aimed to determine the comparison of the amount of Candida albicans colony on heat-cured acrylic and thermoplastic nylon resin after immersed in the Ulee Kareng coffee (Coffea robusta). Methods: The number of specimens in this study were 8 specimens; 4 MeliodentÂ® heat-cured acrylic resins and 4 Bio ToneÂ® thermoplastic nylon resins with size of 10x10x2 mm. The methods of this study was experimental laboratory. The specimens were stored in a solution of Ulee Kareng coffee (Coffea robusta) for 7 days. Each specimen was contaminated with Candida albicans, then the number of Candida albicans colony was counted with Colony counter, from threshing results of heat-cured acrylic and thermoplastic nylon resins. Data were analyzed with unpaired t test. Results: Unpaired t test results showed that there were significant differences (p<0.05) between the number of colonies of Candida albicans in heat-cured acrylic resin (4.5 CFU/ml) and thermoplastic nylon resin (1.5 CFU/ml) after both immersed in the Ulee Kareng coffee (Coffea robusta). Conclusion: The amount of Candida albicans colony on heat-cured acrylic resin was higher than on thermoplastic nylon resin.